2010
DOI: 10.1021/la100785r
|View full text |Cite
|
Sign up to set email alerts
|

Biorefinery: A Design Tool for Molecular Gelators

Abstract: Molecular gels, the macroscopic products of a nanoscale bottom-up strategy, have emerged as a promising functional soft material. The prospects of tailoring the architecture of gelator molecules have led to the formation of unique, highly tunable gels for a wide spectrum of applications from medicine to electronics. Biorefinery is a concept that integrates the processes of converting biomass/renewable feedstock and the associated infrastructure used to produce chemicals and materials, which is analogous to pet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 82 publications
(76 reference statements)
0
69
0
1
Order By: Relevance
“…He has published 4220 refereed research papers. Such gels are attractive candidates for a diverse range of applications in a number of diverse fields, including the design and synthesis of biomaterials, [16][17][18][19][20][21] nano-materials, [22][23][24][25][26][27][28][29][30][31] stimuliresponsive materials, 32 sensors, [33][34][35][36] and templating components for inorganic or organic nanostructures, 37 as well as in molecular electronics [38][39][40][41] and catalysis. Extensive research efforts towards the evolution of novel properties utilizing the underlying principles of self-assembly (i.e., hydrogen bonding, p-p stacking, solvophobic effects, van der Waals forces, charge-transfer interactions and metal-ligand coordination) as a key route has led to the generation of a vast area of research known as supramolecular chemistry.…”
Section: Santanu Bhattacharyamentioning
confidence: 99%
See 2 more Smart Citations
“…He has published 4220 refereed research papers. Such gels are attractive candidates for a diverse range of applications in a number of diverse fields, including the design and synthesis of biomaterials, [16][17][18][19][20][21] nano-materials, [22][23][24][25][26][27][28][29][30][31] stimuliresponsive materials, 32 sensors, [33][34][35][36] and templating components for inorganic or organic nanostructures, 37 as well as in molecular electronics [38][39][40][41] and catalysis. Extensive research efforts towards the evolution of novel properties utilizing the underlying principles of self-assembly (i.e., hydrogen bonding, p-p stacking, solvophobic effects, van der Waals forces, charge-transfer interactions and metal-ligand coordination) as a key route has led to the generation of a vast area of research known as supramolecular chemistry.…”
Section: Santanu Bhattacharyamentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21]23,24,30,32,[35][36][37]42,43,[45][46][47][48][49][50][51][52][55][56][57][58][60][61][62][63][64][65][66][68][69][70][71][72][73][74][75] However, there is no review that addresses the interesting topic of sugar-derived gels. There are several review articles in the contemporary literature on various aspects of gels.…”
Section: Santanu Bhattacharyamentioning
confidence: 99%
See 1 more Smart Citation
“…Their recent work on conjugated dicarboxylate anodes and lithium salt of tetrahydroxybenzoquinone suggested a possible alternative to current inorganic based electrodes212223. Recent research on biobased materials demonstrated the prudent use of biomass for value-added chemicals and products in a biorefinery concept2425. Here, we report a novel organic electrode material for lithium ion batteries, purpurin , which has been extracted from a common plant Madder , most often used as a dye for fabrics.…”
mentioning
confidence: 97%
“…Supramolecular gels have been studied as soft materials for use in applications such as drug-delivery systems, tissue engineering, sensing devices, separation and optoelectronic devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The incorporation of labile metals or anions within these supramolecular gels is of particular importance because metallogels and coordination polymer gels with metal-organic framework structures have widespread applications in areas such as redox responsiveness, 18,19 catalytic action, 20,21 absorption, 22,23 emission, 24-27 magnetism, 23 and electron emission. 21 In addition, the gels composed of a metal-organic framework (MOF) structure can be rapidly, efficiently, and easily prepared under mild conditions in comparison to a typical crystalline MOF with similar properties.…”
mentioning
confidence: 99%